A case of intellectual disability reveals a novel mutation in IQSEC2 gene by whole exome sequencing. (December 2019) - Zou, Qianqian; Zheng, Jie; Zhang, Ruiping; Fang, Yulian; Cai, Chunquan
Abstract : Intellectual disability refers to significantly subaverage intellectual function (intelligence quotient < 70) with impairment of adaptive function. The IQSEC2 gene is one of the pathogenic genes located on chromosome Xp11.22. IQSEC2 is an X-linked gene correlated with intellectual disability and epilepsy. In this study, we reported a 2-year-old male patient presented with reacting sluggishly with people and surroungdings. Active electroencephalogram showed the background of epileptic activity. Brain MRI revealed patchy hyperintensity of bilateral parietal lobe white matter on fluid-attenuated inversion recovery image and widened ventricle, cistern and sulci on T2-weighted image. Delayed myelination was considered. The diagnosis of intellectual disability and epilepsy was made. Whole exome-sequencing was conducted and identified a novel frameshift mutation in exon 15 of IQSEC2 (NM_001111125.2: c.4164dupC: p.Ile1389 Hisfs*218). The variant resulted in the deletion of termination codon, and the protein was extended to termination after stretch of 218 amino acids.This study expands the mutation spectrum of IQSEC2 . It supports the published data suggesting that IQSEC2 plays a significant part in patients with intellectual disability and epilepsy. IQSEC2 should be detected in patients with intellectual disability and epilepsy.